Determinants of time trial performance in trained cyclists - van der Zwaard, S.; de Ruiter, C. J.; Jaspers, R. T.; de Haan, A.; de Koning, J. J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Background: Optimizing cycling performance in short and long distance time trials sets different requirements in peak power and endurance capacity within athletes. Purpose: As a first step, we aimed to explore determinants of time trial performance in trained cyclists. For 6 time trials (0.5 - 40km), we determined to what extent time trial performance was related to mean power output in the time trial (POmean), weight, training volume, gross efficiency (GE), maximal oxygen uptake (VO2max) and maximal power output (POmax), the latter obtained with an incremental test. Methods: Nineteen trained male cyclists completed a maximal incremental test and 6 time trials (0.5, 1, 2, 4, 15, and 40km) with the instruction to finish as fast as possible. Linear regression analyses were performed to assess the relationship between finish times in relatively short and long time trials. For every time trial, Pearson`s correlation coefficients were calculated between time trial performance (defined as inverted finish time) and POmean, weight, training volume, GE, VO2max and POmax. Subjects averaged a training volume of 12 ± 4.6 h/wk. Results: Finish times of long time trials (15 and 40km) were strongly related (R2 = 0.67, p<0.01), as well as time on short time trials (0.5 and 1km, R2 = 0.49, p<0.01). However, performance on shortest and longest time trials was not related (R2 = 0.05). POmean was highly related to performance for most time trials (r = 0.99), but only moderate for short time trials (r = 0.44-0.64). Weight was poorly related (r = -0.28-0.19) and training volume poorly or even negatively related to time trial performance (r = -0.53-0.04). GE poorly attributed to performance (r = -0.03-0.35). In addition, VO2max and POmax were both poorly related to the shortest time trial performance (r = 0.10, r = 0.18) and moderately for other trials (r = 0.50-0.65). Conclusion: This study shows that performances in short time trials (associated with peak power) and long time trials (associated with endurance capacity) were not related, which is in line with the concept that performances of different duration set other physiological requirements. Subsequently, time trial performance was highly related to POmean, moderately related to VO2max and POmax and poorly related to weight, training volume and GE. Somewhat lower correlations with POmean and short time trial performance may be due to pacing strategies. Note that in this study, VO2max (which is commonly used as marker of endurance capacity) relates only moderately to endurance performance. We conclude that future research should investigate other physiological variables (e.g. muscle fiber type and/or mitochondrial density) and pacing strategies as determinants of time trial performance.